ANALISIS HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP KELUARGA DENGAN KEMAMPUAN KELUARGA MERAWAT PASIEN PASCA STROKE - tiurmaida simandalahi (Stikes Syedza Saintika Padang, 2018)
Stroke is the third leading cause of death the most common after cardiovascular disease in the United States (WHO, 2014). The death toll reaches 160,000 per year and direct costs of 27 billion US dollars a year. Incidence varies from 1.5 to 4 per 100 population. The purpose of this study was to determine the relationship between the level of knowledge and attitude of the family with the ability of the family in caring for patients post stroke. This research is analytic with Cross Sectional Study design, conducted from August to September. The population of this study was the entire family of stroke patients who visited the clinic of Mayjhen H.A Thalib Kerinci Hospital with an average visit of 210 people. Sampling technique using Accidental Sampling, as many as 68 people. Data analysis was done univariat and bivariate using Chi Square test.More than half (51.5%) poor family ability, more than half (50.8%) low family knowledge level, more than half (54.4%) negative family attitudes. The result of chi square statistic test shows that there is correlation between family's knowledge level with family ability in caring for post stroke patient obtained p-value = (0.000) there is relationship between family attitudes with family ability in treating post stroke patient obtained p-value = (0.000). Need to do a thorough education to the families of patients on post-stroke patient care through the provision of open class as well as a mini demonstration.Keywords: Stroke; Knowledge; Attitude; Family Ability